Lopinavir/ritonavir: is early administration better in Covid-19? - Bhandari, Sudhir; Sharma, Shrikant; Gupta, Vishal; Bhargava, Abhishek; Rankawat, Govind; Roy, Durgesh (International Journal of Research in Medical Sciences, 2020)
Background: To share the data of coronavirus 2019 (Covid-19) patients started on lopinavir-ritonavir (lopi/r) in relation to time period from the onset of symptoms. Method: Observational descriptive study of 23 Covid-19 patients admitted in a tertiary care center in India from March 2020 to May 2020. Patients categorized into 2 groups based on the timing of initiation of lopi/r from the onset of symptoms. Group 1 were given the drug early (≤7 days) and group 2 late (>7 days). The clinical events (oxygen requirement days and ICU stay) and outcomes of hospital stay between the two groups were evaluated. Results: Patients were started on lopi/r for a period of 14 days on admission, out of which 12 patients were in group 1 and 11 patients in group 2. Underlying co-morbidities were present in 15 patients (65.21%). The mean duration from onset of symptoms to lopi/r initiation was 4 days and 11.1 days in Group 1 and 2 respectively. Requirement for oxygen support (2.16 versus 6.54 days), mean duration of hospitalization (8.58 versus 11.54 days) and mean duration of obtaining first Covid-19 negative report from the onset of symptoms (10.5 versus 19.57 days) were all significantly lesser in group 1 (p<0.05). All patients belonging to Group 1 and eight patients of group 2 recovered completely and were discharged whereas 3 patients of group 2 expired. Diarrhea was the most commonly observed adverse effect of lopi/r in our patients. Conclusion: With no approved weapon to tackle the Covid-19 pandemic, we should keep lopi/r in our armamentarium of drugs and use it at the earliest. More clinical trials are needed in future to ascertain if lopi/r can reduce hospital stay, prompt faster recovery and result in better clinical outcome.